(untitled) (Orfeu, 2020)
The first transitional serial phase, and especially Claudio Santoro’s nationalist period (1949-1960) are characterized by a growing ideological commitment. In the nationalist period, this commitment deepens with the adoption of the norms established in the Second International Congress of Composers and Music Critics, which happened in the city of Prague in 1948 with the aim of defining the style orientation of music in socialist realism. This adoption has profound consequences in Santoro´s style development, causing him to abandon the atonal and serial techniques, favoring the nationalist aesthetic. In this article, we contextualize this style transformation from the symphonic production perspective, defending the thesis that on the Sixth Symphony, the ideology principles are consolidated as well as the composition technique principles adopted in order to defend and practice the nationalist aesthetic. We will approach Santoro’s development of ideological thought. His determinant influences such as the Russian symphonism, will be pointed out, highlighting in musical analysis the influence of The First Viennese School in the composition process of the Sixth Symphony.